Lithium Chloride Protects against Sepsis-Induced Skeletal Muscle Atrophy and Cancer Cachexia - Lee, Ji-Hyung (Cells, 2021)
Inflammation-mediated skeletal muscle wasting occurs in patients with sepsis and cancer cachexia. Both conditions severely affect patient morbidity and mortality. Lithium chloride has previously been shown to enhance myogenesis and prevent certain forms of muscular dystrophy. However, to our knowledge, the effect of lithium chloride treatment on sepsis-induced muscle atrophy and cancer cachexia has not yet been investigated. In this study, we aimed to examine the effects of lithium chloride using in vitro and in vivo models of cancer cachexia and sepsis. Lithium chloride prevented wasting in myotubes cultured with cancer cell-conditioned media, maintained the expression of the muscle fiber contractile protein, myosin heavy chain 2, and inhibited the upregulation of the E3 ubiquitin ligase, Atrogin-1. In addition, it inhibited the upregulation of inflammation-associated cytokines in macrophages treated with lipopolysaccharide. In the animal model of sepsis, lithium chloride treatment improved body weight, increased muscle mass, preserved the survival of larger fibers, and decreased the expression of muscle-wasting effector genes. In a model of cancer cachexia, lithium chloride increased muscle mass, enhanced muscle strength, and increased fiber cross-sectional area, with no significant effect on tumor mass. These results indicate that lithium chloride exerts therapeutic effects on inflammation-mediated skeletal muscle wasting, such as sepsis-induced muscle atrophy and cancer cachexia.